LIFE CYCLE OF THE IDEA OF PLANETARY PERSONALITY - Цзя, Жень (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article deals with the problem of generation and self-deployment of the idea of a planetary personality; the algorithm of self-movement of this phenomenon from the noumenological to the phenomenological horizon in the chain of transformations is recreated: meaning (field) - psychophractal (psyche) - idea (gnoseology) - suggestion / experience (psychology) - ideal (philosophy) - model (science) - competence (education) - ideology (upbringing) - principle (management) - product (technology) - goods (market) – artefact (culture); the life cycle of the idea of a planetary personality is presented, consisting of four stages: 1) origin: meaning - psychophractal; 2) formation: idea - ideal: personality and society - model; 3) functioning: product - competency - ideology - criterion - principle - goods - integrator of social interaction - a means of pressure, aggression, war; 4) climbing: artefacts of planetary geoculture;